Physical activity in free time of physical education teachers in Tarnów - Ziemba, Anita (Health Promotion & Physical Activity, 2019)
Aim: The goal of the study was to evaluate the physical activity of physical education teachers from Tarnów schools in their free time. Material and methods: The research is of pilot nature and was carried out in 2018 among 30 teachers, in the 30–50 age group, teaching physical education in primary schools, junior high schools and high schools in Tarnów. The research covered the participants of the subject workshops. The research was carried out by means of a diagnostic survey and a survey technique was used to obtain necessary information and data. Results: Physical education teachers willingly undertake physical activity during their free time, however, it is usually recreational activity. The teachers most eagerly practice once or twice a week. Male teachers showed greater frequency of physical activity. Practicing sports in the past is reflected in the approach to taking care of health and maintaining physical fitness later in life. The way of spending free time of the examined teachers differs depending on gender. Conclusions: Systematic participation of physical education teachers in physical activities is not satisfactory, and yet the teacher should set an example and make students aware of how to care for body and physical health.